Oil price passthrough to consumer price inflation in South Africa: the role of the inflation environment - Eliphas Ndou; Nombulelo Gumata (Journal of Applied Economics)
This paper estimates various inflation threshold and structural VAR models to investigate the passthrough of oil prices to consumer price inflation in South Africa when inflation is in the 3–6 percent inflation target band compared to when it is above 6 percent. The paper uses monthly data from 2001M1 to 2022M12. We find that the oil price passthrough to inflation is about three times lower when inflation is within the 3–6 percent target band compared to when it is above the 6 percent. Thus, under the inflation targeting framework, the 3–6 percent inflation target band has induced a structural change in the oil price and inflation relationship in South Africa. In addition, a one percentage point oil price inflation shock raises inflation by 0.11 percentage points when inflation is below 4.5 percent compared to 0.43 percentage points above this threshold. These findings imply that the oil price passthrough coefficient in the Bank forecasting model should be half the size when inflation is within 3-6 percent compared to when inflation is above 6 percent.